9+6u=7u+3

Simple and best practice solution for 9+6u=7u+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+6u=7u+3 equation:



9+6u=7u+3
We move all terms to the left:
9+6u-(7u+3)=0
We get rid of parentheses
6u-7u-3+9=0
We add all the numbers together, and all the variables
-1u+6=0
We move all terms containing u to the left, all other terms to the right
-u=-6
u=-6/-1
u=+6

See similar equations:

| -41=-5-6y | | -5x(7x-9)-6=144 | | −76=4x+4 | | 0.8x+1=2+0.75x | | -x2–8x+2=0 | | -2(p+7)=-8 | | a=2a–24 | | X-4+5x=8 | | 1,045=(x+30)11 | | 6x–18=x–3 | | 3+(5h+2)4=3+(5h+2)⋅4 | | 2(h+3)=+2 | | 65/6=x+5/6 | | 5v-35=-7(v-7) | | 7(m-6m=10 | | 52=15x-3 | | 2x+7(x–10)= | | x-14(x·-7)=-84 | | 9-10x=79 | | 2/7-5/6+5/7y=11/6 | | 3x=6x(3x-1) | | 10+u=-7 | | 2x^2+20=-78 | | -2(1-5v=28 | | 99=-2x+3 | | (5/2)=x/(1/7 | | 116=7y+6+4y | | 24-5-10a=3(4-7a) | | 7w+5(w+5)=36 | | x-1.7=8.3 | | 18=1/2(6x+24) | | k/8=14 |

Equations solver categories